Going Critical : The First North Korean Nuclear Crisis - Wit, Joel S.; Gallucci, Robert L.; Poneman, Daniel (Book collections on Project MUSE., 2004)
In this work, three former US officials who played key roles in the 1994 crisis trace the intense efforts that led North Korea to freeze - and pledge to ultimately dismantle - its dangerous plutonium production programme, while avoiding a second Korean War.